On the Validity of Purchasing Power Parity: Evidence from Energy Exporting Sub-Saharan Africa Countries - Ntokozo Patrick Nzimande; Marcel Kohler (SPOUDAI - Journal of Economics and Business, 2016)
Substantial amount of studies have examined the validity of mean-reversion on the real exchange rate. However very limited studies of this nature have been conducted in Sub-Saharan Africa countries, particularly energy exporting countries, hence this study endeavors to find evidence for or against the mean-reversion of the real exchange rate. There is, however inadequate data required for the statistical significance for Sub-Saharan African currencies. Hence this study uses a panel of 5 energy exporting countries, i.e. South Africa, Mozambique, Congo Republic, Nigeria and Angola, to examine the validity of the purchasing power parity. Relying on the Im, Pesaran and Shin and the Fisher ADF proposed panel unit root tests the study fails to reject the null hypothesis of a unit root when small sample size is employed however by extending sample size and employing different price index, i.e. traded goods prices instead of GDP deflators the study reject the null hypothesis of a unit root and hence concludes the purchasing power parity holds in Sub-Saharan African energy exporting countries considered in the study.
Keywords: F31; 330; Purchasing Power Parity; exchange rate; energy; unit root; Africa